Distinct epicardial gene regulatory programs drive development and regeneration of the zebrafish heart - Weinberger, M; Simões, FC; Gungoosingh, T; Sauka-Spengler, T; Riley, PR (Elsevier, 2024)
Unlike the adult mammalian heart, which has limited regenerative capacity, the zebrafish heart fully regenerates following injury. Reactivation of cardiac developmental programs is considered key to successfully regenerating the heart, yet the regulation underlying the response to injury remains elusive. Here, we compared the transcriptome and epigenome of the developing and regenerating zebrafish epicardia. We identified epicardial enhancer elements with specific activity during development or during adult heart regeneration. By generating gene regulatory networks associated with epicardial development and regeneration, we inferred genetic programs driving each of these processes, which were largely distinct. Loss of Hif1ab, Nrf1, Tbx2b, and Zbtb7a, central regulators of the regenerating epicardial network, in injured hearts resulted in elevated epicardial cell numbers infiltrating the wound and excess fibrosis after cryoinjury. Our work identifies differences between the regulatory blueprint deployed during epicardial development and regeneration, underlining that heart regeneration goes beyond the reactivation of developmental programs.